In vivo expression of natural killer cell inhibitory receptors by human melanoma-specific cytolytic T lymphocytes. - Speiser, D; Pittet, M; Valmori, D; Dunbar, R; Rimoldi, D; Liénard, D; MacDonald, H; Cerottini, J; Cerundolo, V; Romero, P (1999)
Natural killer (NK) receptor signaling can lead to reduced cytotoxicity by NK cells and cytolytic T lymphocytes (CTLs) in vitro. Whether T cells are inhibited in vivo remains unknown, since peptide antigen-specific CD8(+) T cells have so far not been found to express NK receptors in vivo. Here we demonstrate that melanoma patients may bear tumor-specific CTLs expressing NK receptors. The lysis of melanoma cells by patient-derived CTLs was inhibited by the NK receptor CD94/NKG2A. Thus, tumor-specific CTL activity may be decreased through NK receptor triggering in vivo.